Abay’s Legacy to the Philosophy of Education - Shon, Peter (NUGSE Research in Education, 2(1), 2017)
As early as the nineteenth century, Abay Kunanbayev foresaw the need to adapt to the world being altered by the hands of geopolitical powers. Rather than to be swept away by the waves of colonial influences, he became the lonely voice in the wilderness urging the Kazakhs to become educated multi-lingually. Though Abay is revered as the country’s foremost philosopher and poet, his writings are mostly covered in secondary school Kazakh Literature courses; though often quoted, the work of Abay is seldom read in its entirety. In addition, information about the impact of his writings on present-day educators in Kazakhstan is lacking. The purpose of this paper is to describe and juxtapose the main ideas in Abay’s The Book of Words, first published in 1909, with various philosophers from the West to examine the relevance of his philosophy in today’s Kazakhstani society. This paper is a historical description which seeks to answer the metaphysical, epistemological, and pedagogical questions under the themes of man, knowledge, and education. This study will contribute to bringing a further spotlight on Abay, not only as a steppe philosopher and poet of the past, but as a philosopher in education for contemporary Kazakh society.
Keywords: Abay; knowledge; soul; education; man; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education